Isolated strains from water sampled during the PHYCOB cruise in the Southwestern Black Sea in 2021 - Urban Tillmann; Bernd Krock (PANGAEA, 2024)
On board microscopic analyses of live net tow (vertical net tows of the upper water column from 30 m depth with a 20 μm mesh-size phytoplankton net) and rosette water samples was performed to characterise the plankton communities, and to document the dinophyte species composition by photo- and video recording. In addition, these samples were used to establish various algal cultures by manual isolation of single cells into 96 well plates filled with 0.3 ml of filtered seawater from the sampling site. Plates were incubated at 20 °C and moderate light intensity (50 μE m-2 s-1), and successfully growing strains were then upscaled into 70 ml plastic culture flasks for further taxonomical and toxicological characterization.
In: Krock, Bernd; Tillmann, Urban; Möller, Kristof; Koch, Florian; Dursun, Fuat; Boicenco, Laura; Vlas, Oana; Dzhembekova, Nina; Mutlu, Sabri; Aslan, Ertugrul (2024): Data collection of the PHYCOB cruise with focus on harmfula algal species in the Southwestern Black Sea in 2021 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963976